Anaemic crisis in sickle cell disease. Issue 5 (May 1975) - Mann, J R; Cotter, K P; Walker, R A; Bird, G W; Stuart, J
Abstract : Sixteen episodes of acute anaemia necessitating urgent blood transfusion have been investigated in 13 children with sickle cell anaemia. In five out of seven episodes there was evidence of increased haemolysis while in 10 out of 16 episodes a profound fall in reticulocyte count indicated marrow erythroid cell failure. Cold agglutinins active at room temperature were detected in 13 episodes, and anti-I specificity was demonstrated in 11. Warmed blood of homologous ABO and Rhesus groups was administered without complication despite difficulty with cross-matching. The exacerbation of anaemia was not due to folate lack, glucose-6-phosphate dehydrogenase deficiency or splenic sequestration, and an infectious agent appeared responsible. The degree of anaemia in homozygous sickle cell disease is usually constant during asymptomatic periods. An episode of sudden profound anaemia (anaemic crisis) may, however, result from marrow hypoplasia, an exacerbation of haemolysis, splenic sequestration, or folate deficiency.